OVERVIEW OF THE MORAL CONCEPTS OF CONFUCIANISM - Ruzmatova Gulnoz Mirakhrarovna (Western European Studies, 2024)
The cultural traditions of the Far East have been forming their own philosophy, not inferior to the level of logical-discursive conceptuality and the problem area of Western European philosophy. One of the most important components of Far Eastern traditions is philosophical thinking. One such philosophical thought is Confucianism, and we can see its spread in South Korea and its influence on the social and political life of the country. In today's modern economic development trends, the role of Confucianism in the civilizational rise in South Korea is huge. In order to understand Confucianism in modern South Korea, it is of course extremely important to study the ancient Chinese cultural world and, in connection with it, the historical roots of Confucianism. The fact that we can still enjoy the advanced philosophical, ethical, scientific and social ideas of Confucianism in South Korea is the basis for the relevance of the topic.
Keywords: Confucius; Confucianism; order; morality